1993
DOI: 10.1007/bf01102192
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of sex knowledge among hearing and deaf college freshmen

Abstract: This study was designed to determine whether there are disparities in sex knowledge between hearing college freshmen at the University of Maryland (N=75) and Loyola College in Baltimore (N=128) and deaf college freshmen at Gallaudet University (N=38). The Sex Knowledge Inventory was administered along with the Knowledge portion of the Sex Knowledge and Attitude Test. The Sex Knowledge Inventory measured knowledge of such topics as masturbation, homosexuality, reproduction, birth control, anatomy and physiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Although our analysis does not indicate why Deaf and hard of students are more likely to report physical partner abuse and psychological partner abuse than hearing students, it has been suggested that Deaf and hard of hearing students in particular have "historically lacked access to comprehensive health and sex information" (Anderson & Kobek Pezzarossi, 2012: p. 276) and given limited information from their parents and teachers often "rely on their peers to obtain healthand-sex related information" Kobek Pezzarossi, 2012, p. 276 citing Fitz-Gerald andFitz-Gerald, 1985;Job, 2004;Swartz, 1993). Accordingly, the heightened levels of psychological and physical abuse among Deaf and hard of hearing college students may be explained in part by limited intimate partner violence health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although our analysis does not indicate why Deaf and hard of students are more likely to report physical partner abuse and psychological partner abuse than hearing students, it has been suggested that Deaf and hard of hearing students in particular have "historically lacked access to comprehensive health and sex information" (Anderson & Kobek Pezzarossi, 2012: p. 276) and given limited information from their parents and teachers often "rely on their peers to obtain healthand-sex related information" Kobek Pezzarossi, 2012, p. 276 citing Fitz-Gerald andFitz-Gerald, 1985;Job, 2004;Swartz, 1993). Accordingly, the heightened levels of psychological and physical abuse among Deaf and hard of hearing college students may be explained in part by limited intimate partner violence health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…This view is likely related to Rohleder and Swartz's (Rohleder & Swartz, 2011) comment that discussing sexuality for disabled individuals makes educators and people without a disability anxious. Interestingly enough, this work related to Deaf sexual education came from the 1970s, (Fitz-Gerald & Fitz-Gerald, 1976, 1978Neff, 1979;Robinson, 1979), 80s (Fitz-Gerald & Fitz-Gerald, 1985), and 90s (Glannon, 1998;Joseph, Sawyer, & Desmont, 1995;Swartz, 1993). Most of this research focused on Deaf sexual education as disseminated by educators and hearing parents.…”
Section: Misconceptionsmentioning
confidence: 99%
“…MacLeod-Gallinger (1992) reported that American Deaf women who obtained tertiary education experienced significantly higher underemployment and unemployment in comparison to Deaf men or hearing peers. Swartz (1993) reported a gender difference in sex knowledge among American Deaf university students. Meanwhile, Fitz-Gerald and Fitz-Gerald (1978) noted that young Deaf women in the United States were made to feel more concerned with their reputation in school and experienced greater guilt in relation to their behaviours.…”
Section: The Experiences Of Deaf Womenmentioning
confidence: 99%
“…Deaf university students have also been show less likely to get tested for sexually transmitted diseases or change their sexual behaviour to decrease risk (Bat-Chava et al, 2005;Woodroffe et al, 1998). Swartz (1993) found that when administered the Sex Knowledge Inventory to students at three different universities, the Deaf university students lagged behind their hearing counterparts in "nearly every aspect of sex knowledge examined" (p. 129). He identified anatomy and physiology as the areas where Deaf students demonstrated the least amount of knowledge.…”
Section: Deaf Students and Sexuality Educationmentioning
confidence: 99%
See 1 more Smart Citation